2018
DOI: 10.1152/ajpcell.00205.2017
|View full text |Cite
|
Sign up to set email alerts
|

Autocrine IL-1β mediates the promotion of corneal neovascularization by senescent fibroblasts

Abstract: Our previous study has confirmed that senescent fibroblasts promote corneal neovascularization (CNV) partially via the enhanced secretion of matrix metalloproteases (MMPs). However, the regulation of MMPs expression in senescent fibroblasts remained unclear. In this study, we identified that the expression and secretion levels of interleukin-1β (IL-1β) were significantly up-regulated in senescent human corneal fibroblasts than that in normal fibroblasts. Moreover, compared with vehicle-pretreated senescent fib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…A gain-of-function variant in NLRP3 leads to keratitis fugax hereditaria [23], with inflammatory attacks affecting the ocular surface. Additionally, persistent activation of the NLRP3 inflammasome has been found in both pterygium and keloids [24][25][26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…A gain-of-function variant in NLRP3 leads to keratitis fugax hereditaria [23], with inflammatory attacks affecting the ocular surface. Additionally, persistent activation of the NLRP3 inflammasome has been found in both pterygium and keloids [24][25][26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“… 29 , 30 Coincidentally, IL-1β plays a pivotal role in the pathogenesis of inflammation and fibrosis 31 , 32 ; moreover, it amplifies the effects of other cytokines. 18 In liver diseases, the NLRP3 inflammasome activation indirectly induces liver inflammation and fibrosis in a cytokine-dependent manner. 33 In contrast, activation of the inflammasome in hepatic stellate cells directly promotes liver fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“… 15 17 Moreover, recent studies have reported that IL-1β induces apoptosis of corneal stromal cells and participates in the repair of corneal injuries, as well as in corneal neovascularization. 18 , 19 However, the involvement of the NLRP3/IL-1β pathway of macrophages in corneal stromal cell activation and corneal scar formation is yet to be confirmed.…”
mentioning
confidence: 99%
“…However, when clearance of these cells becomes compromised, for example, due to an ageing immune system, they accumulate in tissues [ 2 ]. By their nature, senescent cells secrete a variety of bioactive molecules including chemokines, growth factors and reactive oxygen species (ROS) that engage in autocrine and paracrine interactions to influence the local microenvironment [ 3 , 4 , 5 ]. Senescence can result from excessive mitotic division, also referred to as mitotic ageing, or as a response to severe stress.…”
Section: Introductionmentioning
confidence: 99%